Representation of the concept POPULUS in the latin language (based on the lexicographic sources) - Письменна, Юлія Олександрівна (Київський національний університет імені Тараса Шевченка, 2019)
The article focuses on the study of the lexical representation of the Latin concept POPULUS in lexicographic sources. Based on a comparison of relevant lexicographic articles in the bilingual translation dictionaries as well as observing the synonymous series, the key sememes were highlighted, which shape the determined semantic areas of the concept POPULUS. Semantic area “people as a human community, connected by a common origin” is being interpreted through the notions of ethnicity, nation, nationality; the population of the state or its specific part, region, area; tribe, clan, family, degree of kinship. At the lexical level, this meaning is realized through synonymous series: gens, familia, genus, stirps, prosapia; genus, gens, natio, populus. Semantic area “people as a political community” correlates with the notions of state (Roman state), citizenship, democracy, civil rights; and represented by such words, that reflect the facts of the social and political organization of Ancient Rome, as Senatus populusque Romanus; patricii et plebs. Semantic area "people as a large number of people, crowd", realized by the lexemes of the synonymous series plebs, vulgus, multitudo, turba, tumultus, demonstrates the opposition of personality and the popular mass and is marked by an expressive axiology. The semantic peculiarities of the lexemes that represent the concept POPULUS in the context of historical and cultural realities of Ancient Roman society are analyzed; their specific features and axiological characteristics are determined.

Стаття сфокусована на вивченні лексичної репрезентації концепту POPULUS у латинській мові на матеріалі лексикографічних джерел. На основі зіставлення відповідних лексикографічних статей у двомовних перекладних словниках, а також розгляду синонімічних рядів, виділено основні семеми, які формують стійкі семантичні зони концепту POPULUS. Семантична зона «народ як людська спільнота, пов'язана спільним походженням» у перекладних словниках отримує метатлумачення через поняття етнос, нація, народність; населення держави або його певна частина, область, регіон; рід, сім'я, ступінь спорідненості. На лексичному рівні це значення знаходить реалізацію через синонімічні ряди: gens, familia, genus, stirps, prosapia; genus, gens, natio, populus. Семантична зона «народ як cоціально-політична спільнота» корелює з поняттями держава (Римська держава), громадянство, демократія, громадянські права і репрезентована лексемами, які відображають факти соціально-політичного устрою Стародавнього Риму: Senatus populusque Romanus; patricii et plebs. Cемантична ділянка «народ як велика кількість людей, натовп», яка реалізується лексемами синонімічного ряду plebs, vulgus, multitudo, turba, tumultus, демонструє протиставлення «особистість - народна маса» і позначена виразною оцінністю. Проаналізовано семантичні відмінності синонімічних лексем, які репрезентують концепт POPULUS, у контексті історико-культурних реалій давньоримського суспільства; визначено їх специфічні риси та аксіологічні характеристики.
Репрезентація концепту POPULUS у латинській мові (на матеріалі лексикографічних джерел)
Keywords: concept; populus; conceptual sphere; synonymous series; axiology; концепт; populus; концептосфера; синонімічний ряд; аксіологія